Technical Notes - Investigation of Grain Boundary Phase In Stainless Steel - C. C. Clark; J. R. Mihalisin; K. G. Carroll (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1958)
OBSERVATIONS made in this paper were for the purpose of exploring the anomalous behavior of a particular heat of Type 310 stainless steel. The alloy, of nominal composition 25 pct Cr, 20 pct Ni, was observed to form a grain boundary precipitate at exceedingly high rates. A sheet of this metal, 0.060 in. thick, after cooling in air from 2000°F showed the presence of the grain boundary material, whereas none was found after water-quenching from the same temperature. X-ray techniques were applied without success and, in view of the ex-